2008
DOI: 10.1038/labinvest.3700701
|View full text |Cite
|
Sign up to set email alerts
|

Normal human primary CD4+ T lymphocytes synthesize and release functional osteoprotegerin in vitro

Abstract: Osteoprotegerin (OPG) acts as a decoy receptor for receptor activator of nuclear factor-kB ligand (RANKL) and TNF-related apoptosis-inducing ligand (TRAIL). OPG regulates bone remodeling and the immune response. The primary objective was to decipher, among human peripheral blood mononuclear leukocytes (PBML) that produce OPG, the subset(s) responsible for this synthesis and its regulation. To this end, normal human PBML and CD4-, 8-, 19-, 14-enriched subpopulations were studied in vitro for OPG synthesis. PBML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
(80 reference statements)
2
28
0
Order By: Relevance
“…However, OPG expression was not detected in these cells and P. gingivalis challenge was not able to induce its expression. The lack of capacity by Jurkat T-cells to express OPG even in response bacterial challenge has previously been demonstrated [28], although it has also been reported that normal CD4+ T-cells can produce OPG [29]. This is an interesting point, as T-cell infiltrates in active periodontal lesions could stimulate bone resportion via RANKL, but it is not clear if they would be able to restore the physiological balance by compensatory OPG production that would inhibit osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…However, OPG expression was not detected in these cells and P. gingivalis challenge was not able to induce its expression. The lack of capacity by Jurkat T-cells to express OPG even in response bacterial challenge has previously been demonstrated [28], although it has also been reported that normal CD4+ T-cells can produce OPG [29]. This is an interesting point, as T-cell infiltrates in active periodontal lesions could stimulate bone resportion via RANKL, but it is not clear if they would be able to restore the physiological balance by compensatory OPG production that would inhibit osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Anticoagulated blood was layered over Ficoll-Paque cushions and centrifuged at 400 g for 20 min, according to our previous report. 28 The mononuclear leukocyte fraction was collected at the interface, and was washed and resuspended in a-MEM þ 10% FBS. Mononuclear leukocytes (5 Â 10 6 cells per ml) were then subjected to adherence on plastic Petri dishes.…”
Section: Preparation Of T Lymphocytesmentioning
confidence: 99%
“…[7][8][9] OPG is a key regulator of bone remodeling 5,10 but has also been implicated in tumorigenesis, immunologic pathways, and vascular diseases. 6,7,[11][12][13][14][15] The precise role of OPG in vascular disease is currently controversial.…”
mentioning
confidence: 99%